2016
DOI: 10.1177/0960327116674527
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of bone morphogenetic protein-7 against epithelial injury and matrix metalloproteases upregulation induced by silica in vitro

Abstract: Objective: We investigate the effects of bone morphogenetic protein-7 (BMP-7) on models with silica-induced and macrophage-mediated fibrosis and its possible mechanisms in vitro. Methods: Rat alveolar II epithelial (RLE-6TN) cells were incubated with the supernatant of mouse macrophage-like cells (RAW264.7) and treated with 0, 25, 50, and 100 μg/mL silica. Using Western blotting, the epithelial markers (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Our results of BMP-7 reduced adverse myocardial remodeling MMP9 marker, hypertrophy as well as interstitial and vascular fibrosis. There is only one study that showed BMP-7 reduced MMP9 in an inflammatory silica-induced lung cell line in vitro [54]. Therefore, it is possible that BMP-7 reduced cardiac fibrosis and adverse myocardial remodeling through transforming growth factor (TGF-β1) [4,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Our results of BMP-7 reduced adverse myocardial remodeling MMP9 marker, hypertrophy as well as interstitial and vascular fibrosis. There is only one study that showed BMP-7 reduced MMP9 in an inflammatory silica-induced lung cell line in vitro [54]. Therefore, it is possible that BMP-7 reduced cardiac fibrosis and adverse myocardial remodeling through transforming growth factor (TGF-β1) [4,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting TGF-β1-mediated signaling may be a promising therapeutic option for treating patients with RIF. Previously, BMP-7 has been demonstrated to antagonize TGF-β1-mediated fibrosis through the suppression of EMT in fibroses of a number of different organs, including the lung and liver (29)(30)(31)(32). However, the effects of BMP-7 on EMT in RIF have not yet been determined previously.…”
Section: Discussionmentioning
confidence: 99%